Risk scoring model for lung adenocarcinoma based on PD-L1 related signature reveals prognostic predictability and correlation with tumor immune microenvironment genes was constructed - Li-Fei, Meng; Ren, Si-Meng; Wang, Jun; Zhao, Wei-Jun; Chen, Jian; Hu, Wen-Tao (Frontiers in Immunology, 2025)
BackgroundImmunotherapy has recently become a hot topic in the field of oncology, with PD-L1 playing a crucial role in this area. However, the research on PD-L1 correlation prediction models is not fully understood. The aim of our study was to investigate the role of PD-L1-related genes in lung adenocarcinoma immunity.MethodsThe mRNA and clinical data were obtained from the Cancer Genome Atlas database. DESeq2, Glmnet, forestplot, clusterProfiler and enrichplot were used to analyze the mRNA and clinical data. Western blotting and real-time qRT-PCR were used to confirm the GPR115, MF12, GREB1L, SPRR1B and LIPK mRNA and protein expression.ResultsFirstly, 562 cases of TCGA lung adenocarcinoma, including 503 of tumor tissue and 59 of normal tissue were collected. The dataset was analyzed using the DESeq2 package of R. 1,251 high- and 285 low-expression genes were obtained. The tumor samples were divided into CD274-high and CD274-low expression samples and 873 genes were up-regulated and 1,010 genes were down regulated between CD274-high and CD274-low samples. Subsequently, the intersection of 1,251 and 873 was taken to obtain 110 genes that were both highly expressed genes in tumors and CD274 high-expression samples. Survival analysis of 110 genes yielded 5 meaningful genes including GPR115, MF12, GREB1L, SPRR1B, and LIPK (p < 0.001). These five genes were used to construct PD-L1 risk predictors. Cytokine-cytokine receptor interaction and IL-17 signaling pathway were involved in the regulation of this risk model factors to lung adenocarcinoma. The level of effector memory CD4 T cells and Type 2 T helper cells were correlated with the risk model factor. Importantly, the PD-L1 risk prediction model could effectively predict the prognosis of patients.ConclusionThe construction of PD-L1 risk model was of great significance for the treatment of lung adenocarcinoma.